A two-dimensional fullerene covalent network, electrochemical synthesis method and photodetector

CN119859809BActive Publication Date: 2026-10-16SHANGHAI JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510009844.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2026-10-16
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

但包括上述方案在内的现有技术中在剥离得到二维C60网络结构的完整性的同时实现高效率、高质量、高产率以及可扩展生产方面仍有待提高

Benefits of technology

[0021] (1) This invention provides an electrochemical synthesis method for two-dimensional fullerene covalent networks. Based on the intercalation expansion process of layered fullerene superlattices, an electrically driven quaternary ammonium salt cation intercalation strategy containing hydrogen protons is adopted, combined with the auxiliary effect of in-situ reduction of solvated protons at the edge of the fullerene superlattice material. The generated hydrogen bubbles destroy the interlayer interaction forces, thereby effectively promoting the rapid and uniform intercalation. A peeling rate of up to 83% has been successfully achieved, greatly shortening the reaction time and efficiently peeling the fullerene superlattice material into gram-scale high-quality two-dimensional C that can be solution-processed. 60 This method not only shortens the peeling time and improves the peeling efficiency, but also enables the efficient batch preparation of two-dimensional C networks. 60 Online materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859809B_ABST
    Figure CN119859809B_ABST
Patent Text Reader

Abstract

This invention belongs to the field of two-dimensional material preparation technology, specifically relating to a two-dimensional fullerene covalent network, an electrochemical synthesis method, and a photodetector. The method includes the following steps: using a fullerene superlattice material as the cathode, an inert material as the anode, and a mixed solution of a hydrogen-containing quaternary ammonium salt and a polar aprotic solvent as the electrolyte solution, electrochemical exfoliation is performed at a constant potential to obtain a large quantity of two-dimensional fullerene networks in a short time. This invention is based on the intercalation and expansion of layered fullerene superlattices, combined with Mg4C... 60 The in-situ reduction assistance of solvated protons at the crystal edge, coupled with the rapid intercalation and expansion of quaternary ammonium salt cations driven by electricity, generates hydrogen bubbles that disrupt the strong interlayer interactions, promoting the rapid and uniform insertion of quaternary ammonium salt cations between layers. This results in a peeling efficiency of up to 83% and a single-layer peeling rate of up to 30%. The resulting two-dimensional C… 60 The covalent network maintains a complete crystal structure and a large size.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of two-dimensional material preparation technology, specifically relating to a two-dimensional fullerene covalent network, an electrochemical synthesis method, and a photodetector, particularly involving Mg4C. 60 Crystals and two-dimensional C 60 Efficient mass synthesis of covalent networks. Background Technology

[0002] Superatoms are artificial clusters composed of the same element or heteroatoms, whose variations in charge, size, and composition allow for extensive functional customization. Since the initial discovery of specific superatoms capable of mimicking the chemical properties of natural atoms, the scientific community has shown great interest in the synthesis of such two-dimensional materials. Further research has demonstrated that the covalent assembly of superatoms can form two-dimensional materials with properties drastically different from those of conventional atomically composed materials. Their unique hierarchical electronic structure leads to the overlap of intra- and inter-cluster molecular orbitals, endowing the materials with entirely new physical properties. Furthermore, because the customizable structure and chemical properties of superatomic clusters are virtually limitless, two-dimensional superatomic materials have the potential to support unknown assembly units.

[0003] Two-dimensional fullerene covalent networks (two-dimensional C 60 Networks are a new type of superatomic material composed of pure carbon clusters (C1, C2). 60 They are interconnected through carbon-carbon (Cc) covalent bonds, forming a hexagonal lattice structure. In this network, each Cc... 60 The molecule is connected to six adjacent carbon atoms by bridging bonds. 60 Molecular connections, including independent C / C single bonds and [2+2] cycloaddition bonds, constitute a two-dimensional periodic nanocluster structure. Notably, the two-dimensional C... 60 The network is an intrinsically pure carbon semiconductor material with a moderate band gap of 1.6 eV, which contrasts sharply with other carbon materials such as semi-metallic graphene and electrically insulating fullerenes. Furthermore, theoretical studies have shown that two-dimensional C… 60 The network exhibits excellent strength, (thermo)dynamic stability, low thermal conductivity, high carrier mobility, and superior photoelectric / thermoelectric properties. For example, density functional theory (DFT) calculations show that a single-layer two-dimensional C network... 60 The network exhibits strong covalent bonding, with an elastic modulus ranging from 50 GPa to 62 GPa. Molecular dynamics (MD) simulations revealed that even at temperatures as high as 800 K, the two-dimensional C... 60 The network remains stable, and its thermal conductivity is 56.63 W / m·K, which is much higher than that of C. 60 The thermal conductivity of the molecule (0.3 W / m·K to 0.4 W / m·K). First-principles calculations reveal that the two-dimensional C 60 The network has an extremely high hole mobility (1242 cm⁻¹).2 ·V -1 ·s -1 This is mainly attributed to the larger effective mass resulting from the flat energy band near the conduction band minimum (CBM). Calculations also show that the two-dimensional C 60 Networks possess in-plane anisotropic, uniform porous structures and cage-like curved surfaces, making them suitable for various fields such as nonlinear optics, solvent separation, energy storage, single-atom catalysis, and biomedicine. However, despite theoretical predictions showing their broad application prospects, the lack of structurally complete two-dimensional C networks with the fewest layers remains a significant challenge. 60 Currently, experimental verification and practical applications of networks still lag far behind theoretical research.

[0004] Since it is extremely difficult to directly assemble fullerene clusters into two-dimensional structures, existing technologies indicate the use of fullerene superlattice materials such as Mg4C. 60 Indirect synthesis of two-dimensional C using crystals as the parent material 60 Networks are a feasible and conventional method. In this method, two-dimensional C 60 The network is formed by interlayer magnesium ions binding together to create an ordered superlattice structure along the stacking direction. However, the strength of the C-Mg bond is between that of a covalent bond and an ionic bond, and is significantly stronger than van der Waals forces. This makes it difficult to separate the two-dimensional C-Mg network using traditional techniques (such as mechanical exfoliation). 60 Network. Meirzadeh et al. proposed that Mg could be synthesized by using chelating acids and subsequent solvothermal reactions. 2+ From Mg4C 60 Partial removal from the crystal results in loosely stacked C atoms. 60 Network block structure. In this case, mechanical peeling can only produce a very small amount of double-layer C. 60 Network. Furthermore, Hou et al. found that the spontaneous diffusion of organic cations in the solvent can disrupt C-Mg bonds and increase interlayer distance, thereby contributing to the development of two-dimensional C... 60 Network stripping. However, this process requires a long reaction time (>168 hours), thus only yielding milligram-scale two-dimensional materials.

[0005] The main challenge in peeling lies in overcoming the strong interlayer interactions in fullerene superlattice materials while preserving the fragile two-dimensional C 60 The integrity of the network structure. However, in existing technologies, including the above-mentioned solutions, the two-dimensional C-axis is obtained through stripping. 60 There is still room for improvement in achieving high efficiency, high quality, high productivity, and scalable production while maintaining the integrity of the network structure. Summary of the Invention

[0006] To address the aforementioned problems, this invention provides a two-dimensional fullerene covalent network, an electrochemical synthesis method, and a photodetector. This method is based on the intercalation expansion of a layered fullerene superlattice, employing an electro-driven strategy of inserting hydrogen-containing quaternary ammonium salt cations, combined with the auxiliary effect of in-situ reduction of solvated protons at the edges of the fullerene superlattice material. The generation of hydrogen bubbles disrupts interlayer interactions, thereby further promoting rapid and uniform intercalation. This method significantly shortens the reaction time, achieving a peeling rate as high as 83%. The peeled two-dimensional C... 60 The network maintains a complete crystal structure with an average lateral dimension of 52.5 μm. 2 The method exhibits a high monolayer ratio (>30%) and an average thickness of only 2.1 nm. It features short exfoliation time, high exfoliation efficiency, and the ability to efficiently prepare two-dimensional C2 materials in large quantities. 60 Advantages of the Internet.

[0007] The present invention solves the above-mentioned technical problems through the following technical solutions.

[0008] One objective of this invention is to provide an electrochemical synthesis method for two-dimensional fullerene covalent networks, comprising the following steps:

[0009] Using fullerene superlattice material as cathode, inert material as anode, and a mixed solution of hydrogen-containing quaternary ammonium salt and polar aprotic solvent as electrolyte solution, electrochemical stripping was performed under constant voltage. Two-dimensional fullerene covalent networks were obtained through in-situ reduction of hydrogen ions driven by electric field and rapid and uniform intercalation of quaternary ammonium salt cations.

[0010] Furthermore, the concentration of the quaternary ammonium salt containing hydrogen protons in the electrolyte solution is 3 mg / mL to 20 mg / mL.

[0011] Furthermore, the hydrogen-containing quaternary ammonium salt is at least one of tetra-n-butylammonium bisulfate, tetra-n-butylammonium hydrogen phosphate, tetra-n-butylammonium bicarbonate, tetra-n-butylammonium hydroxide, and tetra-n-butylammonium hydrofluoride, and the polar aprotic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, 1,3-dimethyl-2-imidazolinone, propylene carbonate, and acetonitrile.

[0012] Furthermore, the constant voltage potential is -4V to -12V, the peeling temperature is -50℃ to 200℃, and the peeling time is 2h to 8h.

[0013] Furthermore, the fullerene superlattice material is an alkaline earth metal-doped fullerene covalently assembled superlattice.

[0014] Furthermore, the alkaline earth metal is Mg, Li, Na, K, or Rb.

[0015] Furthermore, fullerene superlattice materials are embedded in porous foam metal supports as cathodes.

[0016] Furthermore, after electrochemical stripping, the stripped product was shaken and centrifuged at 800 rpm to 1200 rpm for 3 min to 15 min to obtain the initial product. Then, a 2% to 5% H2O2 solution was added for charge quenching, and the product was centrifuged at 3000 rpm to 12000 rpm for 3 min to 15 min to obtain a two-dimensional fullerene covalent network.

[0017] Furthermore, the electrochemical stripping employs a two-electrode system or a three-electrode system.

[0018] The second objective of this invention is to provide a two-dimensional fullerene covalent network prepared by the above-mentioned electrochemical synthesis method, wherein the lateral dimension of the two-dimensional fullerene covalent network is 0.1 μm to 100 μm and the average thickness is 0.8 nm to 10 nm.

[0019] The third objective of this invention is to provide a photodetector, which is prepared using the aforementioned two-dimensional fullerene covalent network as a photoelectric response element.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] (1) This invention provides an electrochemical synthesis method for two-dimensional fullerene covalent networks. Based on the intercalation expansion process of layered fullerene superlattices, an electrically driven quaternary ammonium salt cation intercalation strategy containing hydrogen protons is adopted, combined with the auxiliary effect of in-situ reduction of solvated protons at the edge of the fullerene superlattice material. The generated hydrogen bubbles destroy the interlayer interaction forces, thereby effectively promoting the rapid and uniform intercalation. A peeling rate of up to 83% has been successfully achieved, greatly shortening the reaction time and efficiently peeling the fullerene superlattice material into gram-scale high-quality two-dimensional C that can be solution-processed. 60 This method not only shortens the peeling time and improves the peeling efficiency, but also enables the efficient batch preparation of two-dimensional C networks. 60 Online materials.

[0022] (2) The electrochemical synthesis method provided by this invention, after stripping two-dimensional C 60 The network retains its complete crystal structure, with an average lateral dimension of 52.5 μm. 2 The single-layer ratio exceeds 30%, and the average thickness is only 2.1nm.

[0023] (3) Due to the two-dimensional C after peeling 60 The network has a unique hierarchical electronic structure, and C 60 It exhibits excellent light-matter interactions, therefore, it can be based on two-dimensional C 60Network materials were used to fabricate thin-film photodetectors, exhibiting a broad-spectrum light response from 405 nm to 1200 nm, with a peak photocurrent at 850 nm and stable and reproducible response time. This efficient top-down synthesis strategy opens new avenues for the development of functional two-dimensional superatomic carbon composite materials and devices. Attached Figure Description

[0024] Figure 1 This is a diagram illustrating the electrochemical synthesis process of the two-dimensional fullerene covalent network of this invention.

[0025] Figure 2 The present invention is Mg4C 60 Material preparation process diagram.

[0026] Figure 3 Mg4C prepared for this invention 60 Physical images and scanning electron microscope images of crystalline materials. Figure 3 'a' in Mg4C 60 Crystal image, b is Mg4C 60 Scanning electron microscope image of the crystal.

[0027] Figure 4 Mg4C prepared for this invention 60 Raman spectrum and X-ray diffraction pattern of the material, Figure 4 In the diagram, 'a' is the Raman spectrum and 'b' is the X-ray diffraction pattern.

[0028] Figure 5 Mg4C prepared for this invention 60 Structural changes during the electrochemical intercalation of crystals. Figure 5 In this context, 'a' represents Mg4C before electrochemical intercalation on nickel foam. 60 Crystal, b is Mg4C after electrochemical intercalation on nickel foam. 60 Crystal.

[0029] Figure 6 Two-dimensional C prepared for this invention 60 Dispersion graph of the network in DMF Figure 6 In the diagram, 'a' is a scatter plot of the actual object, and 'b' is an optical microscope image.

[0030] Figure 7 This describes the peeling yield of Embodiment 1 of the present invention under different operating voltages, electrolyte concentrations, and peeling times. Figure 7 In this context, 'a' represents different operating voltages, 'b' represents different electrolyte concentrations, and 'c' represents different stripping times.

[0031] Figure 8 This is a comparison diagram of the peeling methods of Embodiment 1 and Comparative Examples 3 to 4 of the present invention.

[0032] Figure 9This is a two-dimensional C-shaped embodiment of the present invention. 60 A diagram illustrating the topological structure of a network. Figure 9 In the diagram, a is the SEM image at the 10μm scale, b is the SEM image at the 5μm scale, c is the TEM image, and d is the high-resolution TEM image and selected area electron diffraction pattern.

[0033] Figure 10 This is a two-dimensional C-shaped embodiment of the present invention. 60 AFM diagram of the network Figure 10 In this context, 'a' represents a two-dimensional C. 60 Large-scale AFM image of the network, where b is a single-layer two-dimensional C 60 A cross-sectional view of the network thickness.

[0034] Figure 11 This is a two-dimensional C-shaped embodiment of the present invention. 60 Network thickness and size distribution diagram, Figure 11 In the diagram, 'a' represents the thickness distribution and 'b' represents the size distribution.

[0035] Figure 12 Example 1 of the present invention shows Mg4C under different peeling times. 60 Morphological structure diagram of the crystal. Figure 12 In the table, a represents 0 min, b represents 5 min, c represents 10 min, and d represents 15 min.

[0036] Figure 13 This is a topographic image showing the change in interlayer spacing during intercalation in Embodiment 1 of the present invention. Figure 13 In the figures, a and b are morphological images of the initial stage of intercalation exfoliation observed at different scales, while c and d are morphological images of the changes under the assistance of hydrogen ions.

[0037] Figure 14 The X-ray diffraction patterns of Embodiment 1 of the present invention at different stripping times are shown.

[0038] Figure 15 This is a graph showing the stripping yield of different cations under the same conditions according to the present invention.

[0039] Figure 16 For different quaternary ammonium salts and single H in this invention + A comparison of the monolayer exfoliation rate and nanosheet size after ion intercalation.

[0040] Figure 17 Mg4C at different intercalation stages of the present invention 60 Elemental analysis diagram of EDS energy dispersive spectroscopy of the crystal.

[0041] Figure 18 This invention relates to Mg4C intercalation at different reaction times. 60 Line graph showing interlayer spacing and atomic ratio of a crystal.

[0042] Figure 19 The two-dimensional C of this invention 60 Zeta potential plot and X-ray photoelectron spectrum of the network. Figure 19 In the diagram, 'a' represents the Zeta potential and 'b' represents the X-ray photoelectron spectrum.

[0043] Figure 20 The two-dimensional C of this invention 60 Photocurrent response diagram of the network's photodetector.

[0044] Figure 21 The two-dimensional C of this invention 60 Photodetector of the network at different wavelengths.

[0045] Figure 22 The two-dimensional C of this invention 60 The photocurrent performance of the network's photodetector after changes in voltage and light intensity.

[0046] Figure 23 The two-dimensional C of this invention 60 The responsivity diagram of the network's photodetector under different bias voltages. Detailed Implementation

[0047] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0048] It should be noted that the technical terms used in this invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of this invention. Unless otherwise specified, all raw materials, reagents, instruments and equipment used in the following embodiments of this invention can be purchased from the market or prepared by existing methods.

[0049] Two-dimensional fullerene networks are composed of superatomic C 60 Nanoclusters, linked by covalent bonds, are emerging semiconductor materials with unique hierarchical electronic structures. Fullerene superlattice materials, such as Mg4C... 60 Two-dimensional C2C prepared using crystals as the parent material 60 During the network process, the main challenge in stripping lies in overcoming the bulky Mg4C. 60 Stronger interlayer interactions within the crystal, while simultaneously protecting the fragile two-dimensional C 60The structural integrity of the network. However, existing stripping methods require complex and time-consuming reaction processes, which poses a significant challenge to scalable production and widespread application. In other words, there is still a lack of a stripping strategy that is very suitable for high-efficiency, high-quality and excellent scalable production.

[0050] To address the aforementioned problems, this invention provides a hydrogen-assisted electrochemical strategy for rapidly exfoliating fullerene superlattice materials into solution-processable, gram-scale, high-quality two-dimensional C2. 60 Network. Details are as follows:

[0051] An electrochemical synthesis method for a two-dimensional fullerene covalent network includes the following steps:

[0052] Using fullerene superlattice material as cathode, inert material as anode, and a mixed solution of hydrogen-containing quaternary ammonium salt and polar aprotic solvent as electrolyte solution, electrochemical stripping was performed under constant voltage. Through the in-situ reduction of hydrogen ions driven by electric field and the rapid and uniform intercalation of quaternary ammonium salt cations, a two-dimensional fullerene covalent network was obtained.

[0053] This invention is based on the intercalation and expansion process of layered fullerene superlattices. It employs an electrically driven quaternary ammonium salt cation intercalation strategy with hydrogen protons, combined with the auxiliary effect of in-situ reduction of solvated protons at the edges of the fullerene superlattice material. The generated hydrogen bubbles disrupt the interlayer interactions, effectively promoting rapid and uniform intercalation. A peeling rate of up to 83% was successfully achieved, significantly shortening the reaction time and efficiently peeling fullerene superlattice materials into gram-scale high-quality two-dimensional C2 material that can be solution-processed. 60 This method not only shortens the peeling time and improves the peeling efficiency, but also enables the efficient batch preparation of two-dimensional C networks. 60 Online materials.

[0054] In some specific embodiments, the concentration of the quaternary ammonium salt in the hydrogen-containing proton electrolyte solution is 3 mg / mL to 20 mg / mL. Within this concentration range, optimal auxiliary effect of in-situ hydrogen ion reduction can be achieved, avoiding the formation of excessive bubbles leading to two-dimensional C. 60 The fragmentation of the network also avoids low stripping efficiency due to insufficient auxiliary functions.

[0055] In some specific embodiments, the hydrogen-containing quaternary ammonium salt is at least one selected from tetra-n-butylammonium bisulfate, tetra-n-butylammonium hydrogen phosphate, tetra-n-butylammonium bicarbonate, tetra-n-butylammonium hydroxide, and tetra-n-butylammonium hydrofluoride; and the polar aprotic solvent is at least one selected from N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, 1,3-dimethyl-2-imidazolinone, propylene carbonate, and acetonitrile. In a preferred embodiment, the hydrogen-containing quaternary ammonium salt is tetra-n-butylammonium bisulfate, and the polar aprotic solvent is N,N-dimethylformamide. It should be noted that the choice of solvent affects the Mg4C... 60 Another key factor in crystal intercalation and exfoliation is the use of the polar aprotic solvent N,N-dimethylformamide (DMF) as the dispersion solvent in this invention. DMF exhibits strong charge stabilization capabilities, which facilitates the rapid formation of solvated cations, thereby improving exfoliation efficiency. As a dispersion medium, DMF possesses a low boiling point (153°C) and a high dielectric constant (36.7). Furthermore, DMF in Mg4C… 60 It also exhibits excellent wettability on the crystal, with a contact angle of only 6.3°, which facilitates the efficient intercalation of solvated cations composed of tetrabutylammonium bisulfate (TBA·HSO4).

[0056] In some specific embodiments, the electrochemical stripping process employs a constant voltage method, with the operating potential set between -4V and -12V, the stripping temperature between -50℃ and 200℃, and the stripping time between 2 hours and 8 hours. This potential range is higher than that of Mg4C. 60 The minimum potential window (-3.1V) required for crystal intercalation ensures the smooth progress of the intercalation process. Setting the potential range between -4V and -12V achieves optimal cation intercalation effect and best stripping efficiency, while avoiding excessively high potentials that could lead to problems with two-dimensional C. 60 The phenomenon of network fragmentation, thus maintaining two-dimensional C 60 Network structural integrity and high-quality stripping efficiency.

[0057] In some specific embodiments, the fullerene superlattice material is an alkaline earth metal-doped fullerene covalently assembled superlattice. The alkaline earth metal is Mg, Li, Na, K, or Rb. More specifically, the alkaline earth metal-doped fullerene covalently assembled superlattice includes Mg2C. 60 Mg4C 60 LiC 60 Li2C 60 Li4C 60 Li6C 60 Li8C 60 Li 10 C 60 Li 12 C 60NaC 60 Na2C 60 Na4C 60 K3C 60 K6C 60 Or Rb3C 60 .

[0058] To break the strong interlayer interactions, this invention uses Mg4C 60 Taking fullerene superlattice materials as an example, the electrochemical synthesis process is as follows: Figure 1 As shown, typical electrochemical intercalation was performed in a two-electrode system, using platinum foil as the anode and bulk Mg4C as the electrode. 60 Crystals are used as cathodes, based on layered fullerene superlattices (Mg4C). 60 The intercalation and expansion of the crystal were achieved by electrically driven insertion of hydrogen-containing quaternary ammonium salt cations, combined with Mg4C. 60 The auxiliary role of in-situ reduction of protons at the crystal edge solvation. The generated hydrogen bubbles disrupt the interlayer interaction forces, thereby effectively promoting rapid and uniform intercalation, successfully achieving an exfoliation rate as high as 83%, greatly shortening the reaction time, and transforming Mg4C... 60 Highly efficient crystal exfoliation into gram-scale high-quality two-dimensional C60 that can be solution processed 60 This method not only shortens the peeling time and improves the peeling efficiency, but also enables the efficient batch preparation of two-dimensional C networks. 60 Network. Two-dimensional C after stripping. 60 The network retains its complete crystal structure, with an average lateral dimension of 52.5 μm. 2 The single-layer ratio exceeds 30%, and the average thickness is 2.1nm.

[0059] In some specific embodiments, the alkaline earth metal-doped fullerene covalently assembled superlattice is Mg4C. 60 Crystal, Mg4C 60 Preparation method of crystal materials, process diagram as follows Figure 2 As shown, it includes the following steps:

[0060] C 60 The magnesium source and the furnace source are placed in the corresponding high-temperature and low-temperature zones of a dual-temperature zone tube furnace. The high-temperature zone has a temperature range of 550℃ to 650℃, and the low-temperature zone has a temperature range of 450℃ to 550℃. Under vacuum conditions, chemical vapor transport occurs in the transition region between the high-temperature and low-temperature zones to obtain large quantities of high-quality Mg4C. 60 Crystal.

[0061] It should be noted that the synthesis of large-sized blocky Mg4C 60 Single crystals are the key to realizing large-size two-dimensional C 60As a prerequisite for networking, this invention successfully synthesized large-size, highly crystalline quasi-hexagonal Mg4C in the transition region between two temperature zones of a quartz tube using a chemical vapor transport method. 60 Single crystal.

[0062] This invention provides a Mg4C based on dual-temperature zone chemical vapor transport (CVT) technology. 60 A method for high-quality, batch synthesis of crystals. Using C... 60 The magnesium source and the quartz tube were vacuum-sealed at both ends, and then placed in a dual-zone furnace at 650℃~450℃ for 20h~30h. During this process, C 60 One end of the magnesium source is placed in the high-temperature region, and the other end of the magnesium source is placed in the low-temperature region. 60 Crystallization occurs in the transition region between the two processes. A moderate nucleation rate and a relatively long reaction time are crucial for the growth of large single crystals. Optimal magnesium ion diffusion is achieved by placing a sufficient magnesium source in the low-temperature region, while simultaneously preventing the reaction of magnesium with the quartz tube at high temperatures, thus effectively preventing the byproduct Mg2C. 60 Crystal formation. Furthermore, C 60 Keeping it separate from the magnesium source allows unreacted C to... 60 It can be recycled and reused. This method is economical and beneficial for large-scale crystal synthesis.

[0063] In some specific embodiments, C 60 The mass ratio of magnesium source to magnesium is 0.5–1.5:1, the high-temperature zone ranges from 550°C to 650°C, and the low-temperature zone ranges from 450°C to 550°C. The chemical vapor transport time is 20–30 hours. A moderate nucleation rate and a relatively long reaction time are crucial for the growth of large-size single crystals. By placing a sufficient amount of magnesium source in the low-temperature zone, optimal magnesium ion diffusion can be achieved, avoiding the reaction of magnesium with the quartz tube at high temperatures, thereby effectively preventing the byproduct Mg2C. 60 The formation of crystals. Simultaneously, C 60 Keeping it separate from the magnesium source allows unreacted C to... 60 It can be recycled and reused. This method is universal and economical, and is beneficial for large-scale crystal synthesis.

[0064] In some specific embodiments, fullerene superlattice material is embedded in porous nickel foam as a cathode. To ensure effective contact between the bulk fullerene superlattice material and the electrode, the fullerene superlattice material is encapsulated within porous nickel foam.

[0065] In some specific embodiments, after electrochemical exfoliation, the embedded fullerene superlattice material is transferred from nickel foam to a DMF solution. After manual exfoliation by shaking, the initial product is obtained by centrifugation at 800 rpm to 1200 rpm for 3 min to 15 min. Then, a 2% to 5% H2O2 solution is added for charge quenching, followed by centrifugation at 3000 rpm to 12000 rpm for 3 min to 15 min to obtain a two-dimensional C 60 Network, and two-dimensional C 60 The network is dispersed in DMF solution and stored for later use.

[0066] In some specific embodiments, the electrochemical stripping employs a two-electrode or three-electrode system. In a preferred embodiment, the electrochemical stripping uses a two-electrode system in which a Pt sheet electrode serves as the anode.

[0067] In addition, the present invention provides a two-dimensional C 60 A photodetector for a network thin film, using a two-dimensional C2C fabricated by the electrochemical stripping method described above. 60 The network was fabricated as a photoelectric response element.

[0068] Due to the two-dimensional C obtained by peeling 60 The hierarchical electronic structure of the network, and C 60 With its unique light-matter interaction, this all-carbon two-dimensional material-based thin-film photodetector exhibits a broad-spectrum light response ranging from 405 nm to 1200 nm, a peak photocurrent at 850 nm, and stable and reproducible response time. This efficient top-down synthesis strategy paves the way for the development of functional two-dimensional superatomic carbon-based composite materials and devices.

[0069] The above-mentioned method for fabricating a photodetector includes the following steps:

[0070] Provide a doped silicon substrate.

[0071] A SiO2 layer with a thickness of 300 nm is coated on a doped silicon substrate, and a shaped drain and source electrode are fabricated on the SiO2 layer using photolithography.

[0072] A two-dimensional fullerene network thin film with a thickness of 200 nm was prepared on a porous polytetrafluoroethylene filter membrane by vacuum filtration. The film was then transferred to a SiO2 layer to prepare a photodetector.

[0073] In some specific embodiments, the photodetector has a channel width of 200 μm and a length of 10 μm.

[0074] The following specific examples will provide further explanation.

[0075] Example 1

[0076] A two-dimensional C 60 The electrochemical synthesis method of the network includes the following steps:

[0077] S1, Mg4C 60 Crystal preparation: 250 mg of magnesium foil and 200 mg of C 60 Powder containing C is vacuum-sealed at both ends of a quartz tube. 60 One end of the powder was placed in a high-temperature zone (610°C), while the other end containing magnesium foil was placed in a low-temperature zone (510°C). The mixture was heated for 24 hours in a dual-temperature zone furnace (510°C–610°C) under vacuum. Chemical vapor transport occurred in the transition region between the high and low-temperature zones, yielding a large quantity of high-quality Mg4C. 60 Crystalline materials.

[0078] S2. Tetra-n-butylammonium bisulfate and N,N-dimethylformamide (DMF) are mixed to form a tetra-n-butylammonium bisulfate solution with a concentration of 5 mg / mL, which is used as an electrolyte solution.

[0079] S3, 100 mg of Mg4C encapsulated in a porous nickel foam support. 60 A crystal was used as the cathode and a Pt sheet as the anode, both placed in an electrolyte solution. The electrodes were arranged in parallel at a fixed distance of 2.0 cm. Electrochemical stripping was performed at a constant potential of -8 V at room temperature without inert gas protection. Stripping was stopped after 2 hours. After electrochemical stripping, the embedded Mg4C was removed. 60 Crystals were transferred from nickel foam to DMF solution, peeled by manual shaking, and centrifuged at 1000 rpm for 10 min to obtain the initial product. Then, 3% H₂O₂ was added for charge quenching, and the product was centrifuged at 8000 rpm for 10 min to obtain two-dimensional C₂. 60 Network, and two-dimensional C 60 The network is dispersed in DMF solution and stored for later use.

[0080] Example 2

[0081] A two-dimensional C 60 The electrochemical synthesis method of the network includes the following steps:

[0082] S1, Mg4C 60 Crystal preparation: 150 mg of magnesium foil and 120 mg of C 60 Powder containing C is vacuum-sealed at both ends of a quartz tube. 60One end of the powder was placed in a high-temperature zone at 600°C, while the end containing magnesium foil was placed in a low-temperature zone at 500°C. Under vacuum conditions, the mixture was heated for 24 hours in a dual-temperature zone furnace (500°C–600°C). Chemical vapor transport occurred in the transition region between the high-temperature and low-temperature zones, yielding a large quantity of high-quality Mg4C. 60 Crystalline materials.

[0083] S2. Tetra-n-butylammonium bisulfate and N,N-dimethylformamide (DMF) are mixed to form a tetra-n-butylammonium bisulfate solution with a concentration of 15 mg / mL, which is used as an electrolyte solution.

[0084] S3, 100 mg of Mg4C encapsulated in a porous nickel foam support. 60 A crystal was used as the cathode and a Pt sheet as the anode, placed in an electrolyte solution. The electrodes were arranged in parallel at a fixed distance of 2.0 cm. Electrochemical stripping was performed at a constant potential of -6V at room temperature without inert gas protection. Stripping was stopped after 4 hours. After electrochemical stripping, the embedded Mg4C was removed. 60 Crystals were transferred from nickel foam to DMF solution, peeled by manual shaking, and centrifuged at 1000 rpm for 10 min to obtain the initial product. Then, 3% H₂O₂ was added for charge quenching, and the product was centrifuged at 8000 rpm for 10 min to obtain two-dimensional C₂. 60 Network, and two-dimensional C 60 The network is dispersed in DMF solution and stored for later use.

[0085] Example 3

[0086] A two-dimensional C 60 The electrochemical synthesis method of the network includes the following steps:

[0087] S1, Mg4C 60 Crystal preparation: 250 mg of magnesium foil and 300 mg of C 60 Powder containing C is vacuum-sealed at both ends of a quartz tube. 60 One end of the powder was placed in a high-temperature zone at 620°C, while the end containing magnesium foil was placed in a low-temperature zone at 520°C. Under vacuum conditions, the mixture was heated for 20 hours in a dual-temperature zone furnace (520°C–620°C). Chemical vapor transport occurred in the transition region between the high-temperature and low-temperature zones, yielding a large quantity of high-quality Mg4C. 60 Crystalline materials.

[0088] S2. Tetra-n-butylammonium bisulfate and N,N-dimethylformamide (DMF) are mixed to form a tetra-n-butylammonium bisulfate solution with a concentration of 10 mg / mL, which is used as an electrolyte solution.

[0089] S3, 100 mg of Mg4C encapsulated in a porous nickel foam support. 60 A crystal was used as the cathode and a Pt sheet as the anode, both placed in an electrolyte solution. The electrodes were arranged in parallel at a fixed distance of 2.0 cm. Electrochemical stripping was performed at a constant potential of -10 V at room temperature without inert gas protection. Stripping was stopped after 2 hours. After electrochemical stripping, the embedded Mg4C was removed. 60 Crystals were transferred from nickel foam to DMF solution, peeled by manual shaking, and centrifuged at 1000 rpm for 10 min to obtain the initial product. Then, 3% H₂O₂ was added for charge quenching, and the product was centrifuged at 8000 rpm for 10 min to obtain two-dimensional C₂. 60 Network, and two-dimensional C 60 The network is dispersed in DMF solution and stored for later use.

[0090] Comparative Example 1

[0091] A two-dimensional C 60 The electrochemical synthesis method of the network includes the following steps:

[0092] S1, Mg4C 60 Crystal preparation: 250 mg of magnesium foil and 200 mg of C 60 Powder containing C is vacuum-sealed at both ends of a quartz tube. 60 One end of the powder was placed in a high-temperature zone at 600°C, while the end containing magnesium foil was placed in a low-temperature zone at 500°C. Under vacuum conditions, the mixture was heated for 24 hours in a dual-temperature zone furnace (500°C–600°C). Chemical vapor transport occurred in the transition region between the high-temperature and low-temperature zones to obtain Mg4C. 60 Crystalline materials.

[0093] S2. Mix tetra-n-butylammonium bromide and N,N-dimethylformamide (DMF) to obtain a tetra-n-butylammonium bromide solution with a concentration of 5 mg / mL, which will be used as an electrolyte solution.

[0094] S3, 100 mg of Mg4C encapsulated in a porous nickel foam support. 60 A crystal was used as the cathode and a Pt sheet as the anode, both placed in an electrolyte solution. The electrodes were arranged in parallel at a fixed distance of 2.0 cm. Electrochemical stripping was performed at a constant potential of -8 V at room temperature without inert gas protection. Stripping was stopped after 2 hours. After electrochemical stripping, the embedded Mg4C was removed. 60 Crystals were transferred from nickel foam to DMF solution, peeled by manual shaking, and centrifuged at 1000 rpm for 10 min to obtain the initial product. Then, 3% H₂O₂ was added for charge quenching, and the product was centrifuged at 8000 rpm for 10 min to obtain two-dimensional C₂. 60 Network, and two-dimensional C 60The network is dispersed in DMF solution and stored for later use.

[0095] Comparative Example 2

[0096] A two-dimensional C 60 The electrochemical synthesis method of the network includes the following steps:

[0097] S1, Mg4C 60 Crystal preparation: 250 mg of magnesium foil and 200 mg of C 60 Powder containing C is vacuum-sealed at both ends of a quartz tube. 60 One end of the powder was placed in a high-temperature zone at 600°C, while the end containing magnesium foil was placed in a low-temperature zone at 500°C. Under vacuum conditions, the mixture was heated for 24 hours in a dual-temperature zone furnace (500°C–600°C). Chemical vapor transport occurred in the transition region between the high-temperature and low-temperature zones to obtain Mg4C. 60 Crystalline materials.

[0098] S2. Tetra-n-butylammonium hexafluorophosphate and N,N-dimethylformamide (DMF) are mixed to form a tetra-n-butylammonium hexafluorophosphate solution with a concentration of 5 mg / mL, which is used as an electrolyte solution.

[0099] S3, 100 mg of Mg4C encapsulated in a porous nickel foam support. 60 A crystal was used as the cathode and a Pt sheet as the anode, both placed in an electrolyte solution. The electrodes were arranged in parallel at a fixed distance of 2.0 cm. Electrochemical stripping was performed at a constant potential of -8 V at room temperature without inert gas protection. Stripping was stopped after 2 hours. After electrochemical stripping, the embedded Mg4C was removed. 60 Crystals were transferred from nickel foam to DMF solution, peeled by manual shaking, and centrifuged at 1000 rpm for 10 min to obtain the initial product. Then, 3% H₂O₂ was added for charge quenching, and the product was centrifuged at 8000 rpm for 10 min to obtain two-dimensional C₂. 60 Network, and two-dimensional C 60 The network is dispersed in DMF solution and stored for later use.

[0100] Comparative Example 3

[0101] A two-dimensional C 60 The liquid-phase synthesis method for networks includes the following steps:

[0102] S1, C is purified by sublimation. 60 Powder, purified C 60 The powder and Mg powder were mixed and vacuum-sealed in a quartz tube, then placed in a dual-temperature zone furnace at 500℃~580℃ for 20 hours; wherein, Mg powder and C 60The powder mixture was placed in a high-temperature zone at a temperature of 580°C, while Mg4C... 60 Single crystals are grown in a low-temperature region at 500℃, using a Mg:C ratio of 15:1. 60 Molar ratio synthesis of Mg4C 60 Single crystal.

[0103] S2. Dissolve tetra-n-butylsalicylic acid ammonium in N-methylpyrrolidone (NMP) to obtain a saturated solution, and then add Mg4C under an inert atmosphere. 60 The crystals were soaked in a saturated solution of tetra-n-butylsalicylic acid ammonium for more than 7 days. After manual shaking, a mixture was obtained. The mixture was centrifuged at 1000 rpm for 10 min to remove the precipitate, and then centrifuged at 8000 rpm for 10 min to remove the tetra-n-butylsalicylic acid ammonium solution, yielding a two-dimensional C2. 60 Network, 2D C 60 The network is washed with NMP and then dispersed into NMP for later use.

[0104] Comparative Example 4

[0105] A two-dimensional C 60 The mechanical stripping method of the network includes the following steps:

[0106] S1. Growth of Mg4C using chemical vapor transport technology 60 Single crystal: C 60 Powder and Mg powder in Mg:C 60 The mixture was prepared by mixing in a molar ratio of 6:1, grinding into a homogeneous mixture, pressing into sheets, and placing in quartz tubes. The tubes were then sealed under vacuum and placed in a dual-temperature zone furnace at 500℃~600℃ for 24 hours, after which they were cooled to room temperature to obtain Mg4C. 60 Crystalline, highly air-sensitive Mg4C 60 Crystals grow in the low-temperature region of a quartz tube.

[0107] S2, Mg4C 60 The crystals were immersed in a 10% aqueous solution of acetic acid or nitric acid for 2 hours. Subsequently, the crystals were immersed in N-methylpyrrolidone (NMP) at 180°C for 12 hours, thoroughly rinsed with tetrahydrofuran, and vacuum dried at 80°C for 12 hours. The treated crystals were then peeled off using adhesive tape to obtain a double-layered two-dimensional C. 60 network.

[0108] Two-dimensional C prepared in Example 1 and Comparative Examples 1 to 4 60 The network underwent structural and performance testing, and the results are shown below.

[0109] Figure 3 Mg4C prepared for this invention 60 Physical images and scanning electron microscope images of crystalline materials. Figure 3 'a' in Mg4C 60 Crystal image, b is Mg4C 60 Scanning electron microscope image of the crystal. (e.g.) Figure 3 As shown, this invention produces large-size, highly crystalline quasi-hexagonal Mg4C in the transition temperature range of a quartz tube. 60 Single crystal (lateral dimension in millimeters). Bulk Mg4C due to magnesium ion doping. 60 The crystals exhibit a metallic luster.

[0110] Figure 4 Mg4C prepared for this invention 60 Raman spectrum and X-ray diffraction pattern of the crystal. Figure 4 In the diagram, 'a' represents the Raman spectrum, and 'b' represents the X-ray diffraction pattern. For example... Figure 4 As shown, the X-ray diffraction (XRD) pattern exhibits two characteristic peaks at 10.7° and 20.8°, corresponding to (200) and (400) reflectances, and the Raman spectrum is at 1403 cm⁻¹. -1 The area shows a clear C 60 Vibration peak, and at 939 cm⁻¹ -1 and 963cm -1 The presence of a moderate bimodal peak is attributed to the formation of bridging bonds corresponding to the tetracarbon ring stretching mode. These further confirm the single-phase Mg4C... 60 Successful synthesis of crystals.

[0111] In this invention, N,N-dimethylformamide (DMF) was chosen as the dispersion medium, as shown in Table 1, because it has a low boiling point (153°C) and a high dielectric constant (36.7). Furthermore, DMF in Mg4C... 60 It also exhibits excellent wettability on the crystal, with a contact angle of 6.3°, which facilitates the efficient intercalation of solvated cations composed of tetrabutylammonium hydrogen sulfate (TBA·HSO4).

[0112] Table 1. Performance Comparison of Different Dispersion Media

[0113]

[0114] In addition to quaternary ammonium cations (TBA) + In addition to the intercalation of HSO4, the reduction of protons (from HSO4) - (ionization of anions) in two-dimensional C 60 It plays a crucial role in the stripping of the network. Driven by the electric field, these protons move along Mg4C... 60 The crystal edges were originally reduced, and hydrogen bubbles were uniformly generated. The dense hydrogen bubbles disrupted the strong interlayer interactions, promoting TBA. + Rapid and uniform insertion of cations, enabling monolayer or multilayer two-dimensional C60 Effective network stripping. The hydrogen-assisted effect at the cathode effectively prevents the formation of two-dimensional C. 60 Unnecessary oxidation of the network preserved the two-dimensional C obtained from the stripping. 60 Network structural integrity.

[0115] Figure 5 Mg4C prepared for this invention 60 Volume change diagram during crystal electrochemical intercalation. Figure 5 In this context, 'a' represents Mg4C before electrochemical intercalation on nickel foam. 60 Crystal, b is Mg4C after electrochemical intercalation on nickel foam. 60 Crystals. For example... Figure 5 As shown, Mg4C was monitored by in-situ optical imaging. 60 The volume change during the electrochemical intercalation of crystals is caused by applying a voltage of -8.0V, which leads to rapid and significant volume expansion and the generation of dense hydrogen bubbles.

[0116] Figure 6 Two-dimensional C prepared for this invention 60 A graph showing the network distributed in the DMF. Figure 6 In the diagram, 'a' represents the physical dispersion map, and 'b' represents the two-dimensional C-axis. 60 Network optical microscope images. (e.g., images from a network optical microscope.) Figure 6 As shown in a, Mg4C fully expands after intercalation. 60 It disperses easily in DMF, forming a uniform, high-concentration (5 mg / mL) two-dimensional C by simple manual shaking. 60 Network dispersions. For example... Figure 6 As shown in b, this illustrates a closely packed two-dimensional C on a SiO2 substrate. 60 Optical microscope images of the network.

[0117] The stratified yield was calculated by gravimetric method using the filtration method. Figure 7 This is a graph showing the stripping yield of Example 1 of the present invention under different operating voltages, electrolyte concentrations, and stripping times. Figure 7 In this context, 'a' represents different operating voltages, 'b' represents different electrolyte concentrations, and 'c' represents different stripping times. For example... Figure 7 As shown, the hydrogen-assisted electrochemical stripping strategy achieved a stripping yield of up to 83% within 2 hours.

[0118] As shown in Table 2, compared with existing technologies such as Comparative Examples 3 and 4, the exfoliation method of the present invention exhibits significant advantages in terms of shorter exfoliation time, higher exfoliation efficiency, and better scalability. Existing technologies, such as the liquid-phase exfoliation method (Comparative Example 3), rely on the spontaneous and uniform diffusion of organic cations into the intercrystalline layer. This process typically takes more than 7 days and is highly sensitive to many factors such as temperature, oxygen, and crystal quality.

[0119] Table 2 Comparison of the present invention and existing peeling methods

[0120]

[0121] This invention Mg4C 60 The cathode expansion of the crystal enables the mass production of two-dimensional C within 2 hours. 60 The internet provides a fast and efficient method. Figure 8 This is a comparative diagram showing the peeling methods of Embodiment 1, Comparative Examples 3 and 4 of the present invention. (See diagram for reference.) Figure 8 As shown, the stripping time of this method is at least 84 times faster than liquid-phase stripping (Comparative Example 3). Effective cation intercalation enables the stripping efficiency of this method to reach up to 83%, and it is not easily affected by environmental factors, ensuring high reproducibility.

[0122] Furthermore, this invention is highly scalable by using a large amount of Mg4C 60 Crystals and larger electrolytic cells can significantly increase the two-dimensional C 60 Network output.

[0123] The two-dimensional C after exfoliation was studied using scanning electron microscopy (SEM), transmission electron microscopy (TEM), and atomic force microscopy (AFM). 60 The shape and appearance of a network.

[0124] Figure 9 This is a two-dimensional C-shaped embodiment of the present invention. 60 A diagram illustrating the topological structure of a network. Figure 9 In the diagram, 'a' is a SEM image at a 10 μm scale, 'b' is a SEM image at a 5 μm scale, 'c' is a TEM image, and 'd' is a high-resolution TEM image and a selected area electron diffraction pattern. Figure 9 As shown, the SEM images reveal a wide size distribution, with lateral dimensions exceeding 10.0 μm. Electric field-driven rapid cation intercalation and the generation of numerous bubbles did not lead to the formation of two-dimensional C... 60 Excessive fragmentation of the network. Through TEM characterization, two-dimensional C 60 The network exhibits a typical two-dimensional morphology, with its lateral dimensions consistent with the AFM image. As shown in the high-resolution TEM (HR-TEM) image, the bright spheres arranged in a regular hexagonal lattice correspond to C0. 60 Subunit. Selected area electron diffraction (SAED) patterns clearly confirm the hexagonal lattice structure.

[0125] Figure 10 This is a two-dimensional C-shaped embodiment of the present invention. 60 AFM diagram of the network Figure 10 In this context, 'a' represents a two-dimensional C. 60 Large-scale AFM image of the network, where b is a single-layer two-dimensional C 60A cross-sectional view of the network thickness. (e.g.) Figure 10 As shown, based on the profile view in the AFM image, the detached two-dimensional C 60 The network thickness is 1.1 nm, corresponding to the thickness of a single layer.

[0126] Approximately 150 different two-dimensional C-type samples were examined using an optical microscope and AFM. 60 Network samples were statistically analyzed to determine the stripped two-dimensional C 60 The size (length and width) and thickness distribution of the network. Figure 11 This is a two-dimensional C-shaped embodiment of the present invention. 60 Network thickness and size distribution diagram, Figure 11 In the diagram, 'a' represents the thickness distribution map, and 'b' represents the size distribution map. For example... Figure 10 As shown, over 85% of the peeling yielded a two-dimensional C 60 The network size is greater than 40 μm 2 The average thickness is approximately 2.1 nm, equivalent to 2–3 layers. Notably, the proportion of exfoliated monolayers exceeds 30%, which is due to hydrogen bubbles. The generation of hydrogen bubbles further expands the interlayer distance, promoting rapid and uniform insertion of cations.

[0127] The intercalation and exfoliation mechanisms of Mg4C were analyzed in depth. In-situ SEM was used to monitor Mg4C. 60 Morphological changes of crystals at different intercalation stages. Figure 12 These are morphological diagrams of Embodiment 1 of the present invention at different peeling times. Figure 12 In the given values, a represents 0 minutes, b represents 5 minutes, c represents 10 minutes, and d represents 15 minutes. For example... Figure 12 As shown, before intercalation, bulk Mg4C 60 The crystal exhibits a tightly packed, clearly defined layered structure. After applying a constant voltage (-8V) to the working electrode for several minutes, the interlayer spacing of the crystal significantly increases, and the edges become wrinkled.

[0128] Figure 13 This is a topographic image showing the change in interlayer spacing during the intercalation process in Embodiment 1 of the present invention. Figure 13 In the diagrams, a and b represent the morphological changes at the initial stage of intercalation for different sizes, while c and d represent the morphological changes resulting from hydrogen ion-assisted processes. Figure 13 As shown, due to Mg4C 60 The interlayer interactions of the crystal are strong, and the intercalation of cations is not uniform in the initial stage. In contrast, hydrogen ions can more easily and uniformly enter the interlayer. Subsequent in-situ reduction helps to accurately separate a few layers or even a single layer. Bubbles disrupt the ordered interlayer structure, lower the interlayer sliding energy barrier, and facilitate TBA. + Rapid intercalation of cations creates space.

[0129] Figure 14 The images show X-ray diffraction patterns of Embodiment 1 of the present invention at different peeling times. Figure 14 As shown, as the intercalation process proceeds, from the initial Mg4C 60 From crystal (0.83 nm) to intercalated compound (1.08 nm), the interlayer spacing increases significantly.

[0130] Furthermore, under the synthesis method conditions of Example 1, the present invention employs different cations such as Li + Na + TMA + TEA + THA + Impact on peeling efficiency Figure 15 This is a graph showing the stripping efficiency of different cations under the same conditions according to the present invention. For example... Figure 15 As shown, this indicates TBA + It is the most suitable intercalating cation, with a diameter of 0.83 nm, and is compatible with Mg4C. 60 The interlayer spacing of the crystals (0.84 nm) is matched.

[0131] To prove H + and TBA + Regarding the interactions between ions, we excluded H+ in systems containing tetra-n-butylammonium bromide (TBA·Br) (Comparative Example 1) or tetra-n-butylammonium hexafluorophosphate (TBA·PF6) (Comparative Example 2). + . Figure 16 For different quaternary ammonium salts and single H in this invention + A comparison of monolayer exfoliation rate and nanosheet size after ion intercalation. (See figure.) Figure 16 As shown, a single TBA + Cationic intercalation struggles to overcome interlayer interactions, resulting in extremely low exfoliation efficiency and thick layers. Similarly, intercalation solely by H... + Ion-driven interlayer expansion is also limited and insufficient for stripping.

[0132] As can be seen from the above, TBA + Uniform intercalation of cations for two-dimensional C 60 Effective network stripping is crucial, especially for achieving large lateral dimensions and atomic thicknesses. The assisting role of hydrogen ions plays a significant role in the strategy of this invention, utilizing the in-situ reduction of hydrogen ions to break down Mg. 2+ The stronger interlayer interactions established by the ions provide TBA + The uniform and rapid insertion of cations creates a superior interlayer distance. Notably, H... + and TBA + The synergistic effect between ions is a continuous process that gradually progresses from the crystal edge towards the center.

[0133] During intercalation, Mg 2+ Changes in ions affect the fullerene superlattice (Mg4C). 60 Complete stripping of the crystal is also crucial. Figure 17 Mg4C at different intercalation stages of the present invention 60 EDS energy-dispersive spectroscopy elemental analysis diagram of the crystal. (See attached image.) Figure 17 As shown in the figure, it can be seen that as the reaction proceeds, Mg 2+ The ion content gradually decreased. We hypothesize that hydrogen bubbles disrupted the charge balance at the crystal interface, thereby increasing the disorder of the layered structure along the stacking direction, leading to the partial loss of Mg. 2+ Exposure and release of ions. Once an electric field is applied, high concentrations of TBA on the crystal surface... + Ions will also gradually replace Mg 2+ ion.

[0134] Figure 18 Mg4C during the intercalation process of this invention 60 Atomic proportion diagram of a crystal. (e.g.) Figure 18 As shown, when the interlayer spacing increases to a large extent, Mg and C in the intercalation compound... 60 The atomic ratio decreased from 4.03 to 1.83.

[0135] To characterize two-dimensional C 60 The charge states on the network were analyzed by X-ray photoelectron spectroscopy (XPS) and zeta potential. Figure 19 The present invention is Mg4C 60 Zeta potential plot and XPS plot of the crystal. Figure 19 In the diagram, 'a' represents the Zeta potential plot, and 'b' represents the XPS plot. For example... Figure 19 As shown in a, the two-dimensional C obtained by peeling 60 The network's Zeta potential was -35.2 mV, confirming the presence of surface charge, such as... Figure 19 As shown in b, XPS analysis reveals two-dimensional C 60 Residual Mg on the network surface 2+ Furthermore, a characteristic N1s peak at 400.8 eV was observed for the ammonium group, indicating that Mg... 2+ The ionic portion was treated with TBA + Replaced by ions.

[0136] However, two-dimensional C 60 The large amount of counterion residue on the network is detrimental to optoelectronic devices because these ions disrupt the ideal bandgap alignment, reduce carrier mobility, and increase charge recombination rate. Quenching these negative charges with hydrogen peroxide (H₂O₂) neutralized the average Zeta potential to -5.1 mV. High-resolution XPS spectroscopy confirmed that the quenched two-dimensional C 60The absence of sp-hybridized CN (286.8 eV), N 1s (400.8 eV), and Mg 1s (1304.7 eV) peaks on the network surface indicates that TBA... + and Mg 2+ The ions were completely removed.

[0137] To study these two-dimensional C 60 Based on the photoelectric characteristics of networks, this invention fabricates a planar thin-film photodetector using a simple filtering device, comprising the following steps:

[0138] S1. Provide a doped silicon substrate.

[0139] S2. A SiO2 layer with a thickness of 300 nm is coated on a doped silicon substrate. Photolithography is used to fabricate the fused drain and source electrodes on the SiO2 layer.

[0140] S3. Using vacuum filtration, the two-dimensional C of Example 1 is filtered. 60 A two-dimensional C network was prepared on a porous polytetrafluoroethylene filter membrane. 60 Network thin film, two-dimensional C 60 The thickness of the network film is 200 nm, and then it is transferred onto the SiO2 layer to prepare a photodetector. The channel width of the photodetector is 200 μm and the length is 10 μm.

[0141] Figure 20 The two-dimensional C of this invention 60 Photocurrent response diagram of a network thin-film photodetector. (Example) Figure 20 As shown, with molecule C 60 Unlike photodetectors, which are based on two-dimensional C 60 The network devices exhibit a significant photocurrent response under near-infrared (NIR) illumination. This is due to the shortening of the C-axis by the formation of intermolecular covalent bonds. 60 The distance between units enhances electronic coupling.

[0142] In addition, two-dimensional C 60 Networked thin-film photodetectors have achieved a wider spectral photoelectric response, ranging from the visible light region (405 nm) to the NIR region (1200 nm). Figure 21 The two-dimensional C of this invention 60 Photoelectric response diagrams of network thin-film photodetectors at different wavelengths. (Example) Figure 21 As shown, a photocurrent of approximately 15 nA was observed under visible light illumination, slightly higher at 20 nA at 625 nm. Notably, the photocurrent at 850 nm reached 30 nA, 50% higher than under visible light. This is comparable to single-component materials such as ZnTCPP (400 nm–600 nm), TpEtBrCOF (446 nm), and BT-Py. BuOHCompared to (420nm), two-dimensional C 60 The network exhibits superior broadband photoelectric response, particularly with enhanced photoresponse in the NIR region. Importantly, this photoresponse behavior is relatively stable and reproducible, independent of light wavelength.

[0143] Figure 22 The two-dimensional C of this invention 60 The photocurrent performance of a network thin-film photodetector under different voltage and light intensity variations is shown in the graph. Figure 22 As shown in the upper part of the diagram, the photogenerated current increases significantly with increasing applied voltage, which can be attributed to the increased transport velocity of photogenerated carriers as the electric field strength increases. Figure 22 As shown in the lower half of the image, at 850 nm, the increase in light intensity clearly leads to an enhancement of the photocurrent.

[0144] Figure 23 The two-dimensional C of this invention 60 Photoelectric response intensity diagrams of network thin-film photodetectors under different voltages. (Example) Figure 23 As shown, it exhibits a trend consistent with the photocurrent. Measurements under illumination at different wavelengths confirm this relationship, which follows a power law dependence on light intensity (I). p ∝P α The fitting exponent α≈0.69 can originate from the complex processes of electron-hole generation, trapping, and recombination in semiconductors, or from photoelectric mechanisms. This behavior can also be influenced by factors such as interface defects between the semiconductor and the substrate. Using R∝P -(1-α) It can also fit the corresponding photoelectric response intensity very well.

[0145] Therefore, we can know that two-dimensional C 60 The network's broad spectral response stems from a highly delocalized π-conjugated system within its symmetrical cage structure, allowing photons to absorb across the ultraviolet, visible, and near-infrared regions. Polymer symmetry enhances its optical response by enabling multiple absorptions across different spectral regions. Furthermore, its moderate bandgap facilitates exciton formation and broad-spectral electronic transitions, supported by various electronic and orbital coupling effects. The results indicate that the stripped two-dimensional C 60 Networks are feasible for manufacturing large-scale, cost-effective broadband photonic devices.

[0146] It should be noted that when numerical ranges are involved in this invention, it should be understood that both endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described here to avoid redundancy. Although preferred embodiments of the invention have been described, those skilled in the art, once they understand the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of this invention.

[0147] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. An electrochemical synthesis method for a two-dimensional fullerene covalent network, characterized in that, Includes the following steps: Using fullerene superlattice material as cathode, inert material as anode, and a mixed solution of hydrogen-containing quaternary ammonium salt and polar aprotic solvent as electrolyte solution, electrochemical stripping was performed under constant voltage. Through the in-situ reduction of hydrogen ions driven by electric field and the uniform intercalation of quaternary ammonium salt cations, a two-dimensional fullerene covalent network was obtained. The fullerene superlattice material is Mg4C 60 Crystals; The constant voltage potential ranges from -4 V to -12 V, the peeling temperature is room temperature, and the peeling time ranges from 2 h to 8 h.

2. The electrochemical synthesis method of the two-dimensional fullerene covalent network according to claim 1, characterized in that, The concentration of the quaternary ammonium salt containing hydrogen protons in the electrolyte solution is 3 mg / mL to 20 mg / mL.

3. The electrochemical synthesis method of the two-dimensional fullerene covalent network according to claim 1, characterized in that, The hydrogen-containing proton quaternary ammonium salt is at least one of tetra-n-butylammonium bisulfate, tetra-n-butylammonium hydrogen phosphate, tetra-n-butylammonium bicarbonate, tetra-n-butylammonium hydroxide, and tetra-n-butylammonium hydrofluoride; and the polar aprotic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, 1,3-dimethyl-2-imidazolinone, propylene carbonate, and acetonitrile.

4. The electrochemical synthesis method of the two-dimensional fullerene covalent network according to claim 1, characterized in that, Fullerene superlattice material is embedded in a porous foam metal support as a cathode.

5. The electrochemical synthesis method of the two-dimensional fullerene covalent network according to claim 1, characterized in that, The electrochemical stripping uses a two-electrode or three-electrode system. After electrochemical stripping, the stripped product is shaken and centrifuged at 800 rpm to 1200 rpm for 3 min to 15 min to obtain the initial product. Then, a 2% to 5% H2O2 solution is added for charge quenching, and the product is centrifuged at 3000 rpm to 12000 rpm for 3 min to 15 min to obtain a two-dimensional fullerene covalent network.

6. A two-dimensional fullerene covalent network prepared by the electrochemical synthesis method according to any one of claims 1 to 5, characterized in that, The lateral dimensions of the two-dimensional fullerene covalent network range from 0.1 μm to 100 μm, and the average thickness ranges from 0.8 nm to 10 nm.

7. A photodetector, characterized in that, The photoelectric response element was prepared using the two-dimensional fullerene covalent network described in claim 6.

Citation Information

Patent Citations

  • Method for preparing graphene energy storing material through electrochemical cathodic disbonding

    CN102923697A

  • Method for stripping ferric thiophosphate crystal synchronously doped monatomic by electrochemical assistance

    CN113880060A